Oolonghomobisflavans exert neuroprotective activities in cultured neuronal cells and anti-aging effects in Caenorhabditis elegans - Zhang, Shaoxiong; Duangjan, Chatrawee; Tencomnao, Tewin; Wu, Liangyu; Wink, Michael; Lin, Jinke (Frontiers in aging neuroscience, 2022)
Potential health benefits of tea has attracted significant scientific and public attention worldwide. Tea polyphenols are considered as natural promising complementary therapeutical agents for neurodegenerative diseases. However, the anti-neurodegeneration or anti-aging activities of oolong tea polyphenols have not been investigated. The current study aims to document beneficial effects of oolong tea polyphenols [dimers of epigallocatechin gallate (EGCG), oolonghomobisflavan A (OFA), and oolonghomobisflavan B (OFB)] with neuroprotective and neuritogenesis properties in cultured neuronal (Neuro-2a and HT22) cells and Caenorhabditis elegans models. In vitro, we found that the compounds (EGCG, OFA, and OFB) protect against glutamate-induced neurotoxicity via scavenging radical activity, suppression intracellular ROS and up-regulation of antioxidant enzymes. Moreover, the compounds induce neurite outgrowth via up-regulate Ten-4 gene expression. Interestingly, OFA and OFB exert stronger neuroprotective and neurite outgrowth properties than EGCG known as an excellent antioxidant agent in tea. In vivo, we found that the compounds protect against C. elegans Aβ-induced paralysis, chemotaxis deficiency and α-synuclein aggregation. Moreover, the compounds are capable of extending the lifespan of C. elegans. OFA and OFB possess both anti-neurodegeneration and anti-aging activities, supporting its therapeutic potential for the treatment of age-related neurodegenerative diseases which need to be studied in more detail in intervention studies.
Gesehen am 11.01.2023